Seas of Renewal: Turning Sea Urchin Waste into Polyhydroxynaphtoquinone-Collagen Biomaterials for Regenerative Medicine - Giordana Martinelli; Stefania Marzorati; Margherita Roncoroni; Luciano Magro; Matteo Brilli; Giangiacomo Beretta; Graziano Colombo; Luca Melotti; Anna Carolo; Giulia Zivelonghi; Stefano Farris; Marco Patruno; et al. (Marine Biotechnology, 2025)
Chronic wounds and skin ulcers pose significant challenges to healthcare systems globally, necessitating innovative approaches to accelerate healing processes. Biomaterial-based therapies have emerged as promising solutions for tissue regeneration. This study focuses on valorization of sea urchin waste toward the development and characterization of collagen-based scaffolds added with polyhydroxynaphthoquinone (PHNQ) antioxidants, successfully incorporated into biomaterials at optimal ratio, enhancing scaffold stability and integrity. Water uptake, mechanical properties, and degradation kinetics of the composite scaffolds were evaluated and compared with controls. Biocomposites were also tested for cytotoxicity. Results indicate that composite scaffolds exhibit superior chemical stability and slower degradation rates, attributed to strong interactions between collagen and PHNQs. This aspect was explored also through in silico investigations by means of tight binding molecular dynamics methods. It has been found that a covalent bond forms between the selected collagen representative and one PHNQ. Furthermore, the antioxidant activity of PHNQs was retained in the composite scaffolds, providing additional therapeutic benefits under the perspective application of regenerative medicine. Normal human dermal fibroblasts (NHDF) exposed to the combination of collagen and PHNQs remained viable. Overall, these findings highlight the potential of sea urchin food waste in a valorization chain, offering added value through the production of collagen-based composite scaffolds.

Gene expression and metabolite accumulation during strawberry (Fragaria × ananassa) fruit development and ripening - Paolo Baldi; Saverio Orsucci; Mirko Moser; Matteo Brilli; Lara Giongo; Azeddine Si-Ammour (Planta, 2018)

Fine-tuning of the flavonoid and monolignol pathways during apple early fruit development - Paolo Baldi; Mirko Moser; Matteo Brilli; Urska Vrhovsek; Massimo Pindo; Azeddine Si-Ammour (Planta, 2017)

Identification of herbaceous hosts of the Grapevine Pinot gris virus (GPGV) - Valeria Gualandri; Elisa Asquini; Pierluigi Bianchedi; Laura Covelli; Matteo Brilli; Umberto Malossini; Paola Bragagna; Pasquale Saldarelli; Azeddine Si-Ammour (European Journal of Plant Pathology, 2017)

The Origin and Evolution of Operons: The Piecewise Building of the Proteobacterial Histidine Operon - Renato Fani; Matteo Brilli; Pietro Liò (Journal of Molecular Evolution, 2005)

Molecular Evolution of hisB Genes - Matteo Brilli; Renato Fani (Journal of Molecular Evolution, 2004)